Factors that influence the commencement of smoking among the youths / Norafidah Saidin - Saidin, Norafidah; Ismail, Norsuhaila (2006)
The increasing prevalence of youths smoking initiation demonstrates the need to identify the commence age of smoking and the factors that influence the commencement age of smoking among the youths.